Neurocritical Care - Hacke, Werner; Hanley, Daniel F.; Einhäupl, Karl M.; Bleck, Thomas P. (Springer Berlin Heidelberg, 1994)
A Quick Reference Text! Easy to read and practical in design, Neurocritical Care is the book specialists will turn to for quick reference. It concentrates on management problems, from diagnostic procedures to therapeutic strategies. Exact descriptions are given for treatment procedures, and it is easy to find the appropriate treatment for a given patient. International Expertise! More than 100 authors from North America have contributed to the book. The different strategies used on either side of the Atlantic have been described, the sections on neuroimaging have been reviewed by a neuroradiologist. Comprehensive in Scope! Both frequent and rare neurological diseases that may require critical care treatment and subjects of more general interest such as monitoring strategies, ethical problems, brain death and neurological disorders in internal medicine have been covered. Pathophysiology is also discussed, insomuch as it is important for understanding the treatment strategies